2016
DOI: 10.1111/liv.13261
|View full text |Cite
|
Sign up to set email alerts
|

Combination of tauroursodeoxycholic acid and N‐acetylcysteine exceeds standard treatment for acetaminophen intoxication

Abstract: These findings indicate that a combination strategy of N-acetylcysteine and tauroursodeoxycholic acid surpasses the standard of care in acetaminophen-induced liver injury in mice and might represent an attractive therapeutic opportunity for acetaminophen-intoxicated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In addition to the presence of its nucleophilic thiol, which could directly target NAPQI-protein adducts, NAC is a precursor of glutathione, stimulating its synthesis by providing the rate-limiting cysteine precursor, and therefore it is conceivable that the protective effect of NAC in VPAþAPAP hepatotoxicity may imply a dual mechanism involving the prevention of NAQPIprotein adduct formation and glutathione replenishment, thereby abolishing the onset of ER stress, consistent with recent findings in fasted mice treated with APAP. 50 The relevance of the ER stress in the hepatotoxicity caused by VPAþAPAP in nonfasted mice is further demonstrated by the time-dependent sequence of events, in which the onset of ER stress by VPAþAPAP preceded liver injury, and by the ability of the chemical chaperone TUDCA to abolish the induction of ER stress markers and protect against VPAþAPAP-mediated liver injury. Interestingly, both NAC and TUDCA prevented the upregulation of STARD1 by VPAþAPAP, consistent with the causal role of ER stress in inducing STARD1 overexpression, underlying a previously unrecognized ER stress-STARD1 axis in APAP hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the presence of its nucleophilic thiol, which could directly target NAPQI-protein adducts, NAC is a precursor of glutathione, stimulating its synthesis by providing the rate-limiting cysteine precursor, and therefore it is conceivable that the protective effect of NAC in VPAþAPAP hepatotoxicity may imply a dual mechanism involving the prevention of NAQPIprotein adduct formation and glutathione replenishment, thereby abolishing the onset of ER stress, consistent with recent findings in fasted mice treated with APAP. 50 The relevance of the ER stress in the hepatotoxicity caused by VPAþAPAP in nonfasted mice is further demonstrated by the time-dependent sequence of events, in which the onset of ER stress by VPAþAPAP preceded liver injury, and by the ability of the chemical chaperone TUDCA to abolish the induction of ER stress markers and protect against VPAþAPAP-mediated liver injury. Interestingly, both NAC and TUDCA prevented the upregulation of STARD1 by VPAþAPAP, consistent with the causal role of ER stress in inducing STARD1 overexpression, underlying a previously unrecognized ER stress-STARD1 axis in APAP hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…APAP overdose-induced liver injury is probably one of the most common causes of drug-induced acute liver failure 30 without effective medication. N-acetylcysteine (NAC) currently is the only drug approved for treatment of APAP overdose-induced liver injury via suppressing ROS at a relatively early stage 31 . IL-22 has been demonstrated to alleviate APAP-induced liver injury; however, the underlying mechanisms remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…NAC seems to detoxify NAPQI toxicity through glutathione supplementation and an anti-oxidative action during APAP hepatotoxicity [ 33 , 34 , 35 ]. Wang et al [22] demonstrated that EtPy has a preventive action on dopamine-induced cell death in PC12 cells, which may be because of the anti-apoptosis action of EtPy.…”
Section: Discussionmentioning
confidence: 99%